Friendliness pays off! Monetary and immaterial gifts in consumer-salesperson interactions - Michael Kirchler; Stefan Palan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
Recent studies find ample evidence that monetary and immaterial gifts influence effort in the workplace. We investigate the impacts of monetary gift exchange and of expressions of respect on salespersons' reciprocity when purchasing doner durum, a common lunch snack. Prior to the food's preparation, we either induce monetary gift exchange by tipping or explore the role of respect by making a compliment. We repeat the interaction on five consecutive days. Our findings show that salespersons exhibit positive reciprocity in response both to a monetary gift and to compliments regarding the product. The "compliment-effect" furthermore increases with repeated visits.
Keywords: D01; D03; 330; gift exchange; respect; natural field experiment